The Effect of Growing Media Variations on Fruiting Body Number and Ash Content of Oyster Mushroom (Pleurotus ostreatus) - Rakhmawati, Reni; Sulistyoningsih, Mei; Susatyo, Ary; Amelia, Steffy (Jurnal Biologi Tropis, 2026)
Oyster mushroom (Pleurotus ostreatus) cultivation relies heavily on sawdust as the primary growing medium, while its availability is becoming increasingly limited, creating a need for alternative substrates derived from recycled materials. This study aimed to evaluate the effects of recycled-material-based growing media om the number of fruiting bodies and the ash content of oyster mushrooms. A quantitative experimental method was employed using a completely randomized design consisting of four treatments and four replications, resulting in 16 experimental units. The treatments were sawdust as the control (A0), used cardboard (A1), marga waste (A2), and a mixture of 50% used cardboard and 50% marga waste (A3). The observed parameters were the number of fruiting bodies and ash content. Data were analyzed using normality and homogeneity tests, followed by One-Way ANOVA and Duncan’s multiple range test at a 5% significance level. The results indicated that the growing media affected fruiting body production, with marga waste (A2) yielding the highest average number of fruiting bodies among all treatments. This effect was statistically significant (p = 0.027). In contrast, ash content showed relatively similar values across treatments and was not significantly affected by the type of growing medium (p = 0.226). In conclusion, marga waste demonstrated the greatest potential for increasing oyster mushroom productivity through enhanced fruiting body formation, while maintaining comparable ash content. These findings highlight the potential of marga waste as a sustainable and cost-effective alternative substrate for supporting environmentally friendly and economically viable oyster mushroom cultivation.